First report of Fusarium tricinctum Causing Leaf Blight on Amorphophallus konjac in Hunan Province of China - Sun, Lei (Plant disease, 2023)
Konjac (Amorphophallus konjac) is a perennial herbaceous plant of the Araceae family, cultivated mainly in south-western China and used extensively for weight loss (Chua et al. 2010). In June 2022, leaf blight was detected on a 2,00 ha A. konjac plantation in Chenxi County, Huaihua City, Hunan Province. It infected almost 20% of the area under cultivation and tends to occur each year during warm, humid weather from May to July, causing significant economic losses to A. konjac production. There were small brown spots on the leaves which gradually spread to form irregular brown lesions. In severe cases the entire plant turned yellow and died. Nine samples were collected randomly from different plants in three plantation forests to isolate the pathogens. They were washed with sterile water and the lesions were excised. They were subsequently disinfected with 3% hydrogen peroxide for 30 s, 75% ethanol for 90 s and rinsed three times with sterile water. The cut sections were then placed on water agar plates and grown in the dark in a constant temperature incubator at 28℃ for 3-5 days, when mycelia grew they were transferred to potato dextrose agar medium and grown in the dark at 28℃ for 3-5 days. Eleven purified fungal isolates were obtained, ten of which looked like Fusarium (90.9% isolation rate), and three representative isolates (MY5, MY7 and MY9) were chosen for further study. The fungal colonies initially appeared white and gradually turnned dark red. Macroconidia were crescent-shaped, elongated, slightly curved and had 2 to 4 septations, with a predominance of 3 septations. They measured 15.540 to 42.083 × 2.760 to 4.558 μm (n=100). Microconidia were oval or pyriform, with a maximum of one septum and measured 6.135 to 24.990 × 2.158 to 4.412 μm (n=100). Two genetic regions, the translation elongation factor-1 (TEF1-α) and RNA polymerase II largest subunit (RPB1) genes, were amplified and sequenced to verify the identity of the fungus (Qiu et al. 2023). The universal primers TEF1-F/R, G2R/Fa were used for amplification and sequencing, and the sequences were submitted to GenBank (TEF1-α: OR545395, OR545397, OR545399; RPB1: OR545394, OR545396, OR545398). A joint phylogenetic tree of the two genes was constructed and analysis showed that the three isolates were significantly clustered with Fusarium tricinctum. Based on the results of morphological identification and phylogenetic tree analysis, the three isolates were identified as F. tricinctum. Pathogenicity tests were carried out on 12 uniformly growing leaf expansion stages of konjac plants，each inoculated with five young leaves. Mycelial blocks of 6 × 6 mm grown on PDA media for 5 days were placed on the surface of the leaves, while sterile PDA blocks were placed on the control plant. After 10 days of rearing the treated plants in a constant temperature chamber at 28°C and 90% relative humidity, the lesions appeared and the pathogens re-isolated from the diseased tissues had the same morphological characteristics as representative isolates. F. tricinctum has been shown to be the major pathogenic fungus causing leaf blight in wheat (Triticum aestivum L.) (Castañares et al. 2011) and orchardgrass (Dactylis glomerata L.) (Wu et al. 2020). To our knowledge, this is the first time in the world that F. tricinctum has been reported to cause leaf blight in A. konjac. This research could provide a foundation for future control of leaf blight disease